1984
DOI: 10.1557/proc-39-411
|View full text |Cite
|
Sign up to set email alerts
|

Alloys based on NiAl for High Temperature Applications

Abstract: This paper presents some of the results obtained in an on-going study of NiAl alloys for potential high temperature applications. Alloys were prepared by powder metallurgy techniques. Flow stress values at slow strain rates and high temperatures were measured. Some promising ternary alloying additions (Hf, Ta and Nb) have been identified. The mechanism of strengthening in alloys containing these additions appears to be a form of particle dislocation interaction. Interesting effects of grain size and stoichiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Elements such as Cr, Mo and Re have limited low temperature solubility «1 %). These elements, when added beyond their solubility limit, precipitate metallic a Cr, -Mo or -Re particles which strengthen NiAl [7]. Microstructure control is achievable with proper solution and aging treatments.…”
Section: High Temperature Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Elements such as Cr, Mo and Re have limited low temperature solubility «1 %). These elements, when added beyond their solubility limit, precipitate metallic a Cr, -Mo or -Re particles which strengthen NiAl [7]. Microstructure control is achievable with proper solution and aging treatments.…”
Section: High Temperature Strengthmentioning
confidence: 99%
“…Nickel alull.J.inide (NiAI) has been the subject of several recent development programs [1][2][3][4][5][6][7]. This overview paper will describe the physical and mechanical properties of NiAI, its application potential, processing issues, and the progress made in improving its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a beneficial effect on the ductility and fatigue crack growth resistance was found in the same investigation for additions of 0.1 and 0.5at.% Zr, but both properties deteriorated again in an alloy with 1at.% Zr. Intermetallics 13 (2005) The mechanical behaviour of Fe-Al alloys with higher Zr contents (O1at.%) was studied by compression tests on alloys of composition Fe-39Al-5Zr, Fe-40Al-2Zr [27], and Fe-47Al-5Zr [28]. The flow stresses at about 1000 8C were found to be significantly increased compared to binary alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we are concerned only with its high temperature mechanical properties. Previous work [5] has shown that the high temperature creep resistance of NiAl can be improved to levels comparable with those of some superalloys by inacroalloying with ternary additions, using a powder metallurgy process. The powder metallurgy process involves blending of elemental ternary additions with binary NiAl followed by hot extrusion in a sealed steel container.…”
Section: Introductionmentioning
confidence: 99%